STRATEGI INOVASI PRODUK GARMEN DALAM MENGHADAPI PASAR BEBAS (STUDI KASUS PADA UKM GARMEN DI KOTA DENPASAR) - Apfita Masi (Ma Chung Press, 2015)
It takes creativity in developing a product that is of high quality and innovative. Small and medium enterprises (SMEs) as they are increasingly recognized as central contributors to innovations play a pivotal role in the national economies of countries all around the world. Same as the other developed and emerging economies in the world, SMEs are important force for economic development especially in Indonesia. This research focuses on strategy of product innovation applied by garment SMEs in Denpasar. Author used qualitative method in this research. Three garments which author studied are Bella Shop, CV Bali International Company, and CV Mama & Leon. Author interested in studying any strategy of product innovation garment products in Denpasar since the amount of exports of their apparel from garments in Bali especially in Denpasar are very big and interesting to study more about the product innovation on their designs and motifs. Because the design and motifs of their garments from Bali known with typical embroidery, motifs, and high artistic value. In this research author will see SME garment’s weaknesses and threats in the competition of the free trade. From the results of this study was found that every product innovation strategy that is applied to the garment SMEs have implications for product innovation theory. The product innovation strategy covers innovation-based design, modulation- based innovation, develop new product attributes, and develop models and sizes of products.